P106 Multidisciplinary assessment of inducible laryngeal obstruction (ILO) & upper airway symptoms in severe Asthma. Single centre experience of service development & outcomes. (11th November 2022) - Higbee, DH; Morgan, C; Dixon, C; Brady, S; Shrimanker, R; Dodd, JW
Abstract : Introduction: ILO is an important co-morbidity and mimic of asthma. Patients with ILO have a high symptom burden and are often inappropriately prescribed asthma treatments (including high dose oral corticosteroids) which are ineffective in treating ILO. ILO is diagnosed using Continuous Laryngoscopy with Provocation/Exercise (CLP/E) and can be effectively treated with speech and language therapy (SALT) based interventions. Method: We provide a multidisciplinary, holistic assessment for patients referred to the severe asthma clinic. For patients with upper airway symptoms further assessment, including CLP/E, is arranged. On the day of CLP/E, patients complete objective questionnaires and have a focused clinical history. In addition, we use the Breathing Pattern Assessment Tool, and in those with a high score indicating breathing pattern disorder (BPD), we measure end-tidal CO2 . CLP/E is performed in Respiratory Physiology which is equipped with a treadmill, exercise bike, and a range of inhaled triggers e.g. perfumes/cleaning products. The CLP/E is undertaken by a respiratory doctor and observed by SALT, and physiologist. We use disposable laryngoscopes to avoid infection control issues. Spirometry is performed before and after CLP/E. Results: We have performed 40 CLE/Ps with no significant adverse events. We found 7 cases of ILO (17.5%), 9 cases of BPD (22.5%), 10 of laryngeal hypersensitivity (25%), 3 of dynamic airway collapse (7.5%), 3 of psychological overlay (7.5%), and 1 patient had a tracheal web. Some patients had more than one of these diagnoses. Treatment with SALT is initiated at the time of testing utilising biofeedback. Conclusion: CLP/E plays an essential role in the investigation and management of patients presenting to the severe asthma clinic. It enables diagnosis of co-morbidities that require MDT treatment. CLP/E is a safe procedure that can easily be performed in an appropriate hospital setting by SALT or doctors trained in bronchoscopy.